Short-Time Work and Precautionary Savings - Thomas Dengler; Britta Gehrke; Leopold Zessner-Spitzenberg (TU Wien, Institute of Statistics and Mathematical Methods in Economics, Research Unit in Economics, 2024)
During the Covid-19 crisis, most OECD countries used short-time work (subsidized reductions in working hours) to preserve employment. This paper documents that short-time work affects the behavior of firms (supply) and households (demand). First, using household survey data from Germany, we show that the consumption risk of short-time work is lower than that of unemployment. Second, we construct a New Keynesian model with heterogeneous workers and firms, incomplete asset markets, and labor market frictions. Short-time work weakens workers' precautionary savings motive and lowers labor costs. This reduces the level and volatility of both the separation and unemployment rate at the cost of tying workers to less productive firms. Quantitatively, the positive employment effects dominate the productivity losses.
Keywords: E21; E24; E32; E52; E62; J63; 330; Short-time work; fiscal policy; incomplete asset markets; unemployment risk; matching frictions